Correlation of weight-based i.v. immune globulin doses with changes in serum immunoglobulin G levels. (15th February 2015) - Anderson, Collin R.; Olson, Jared A.
Abstract: Purpose: Correlations between the i.v. immune globulin (IVIG) dose and the change in serum immunoglobulin G (IgG) concentration with three methods of weight-based dosing were investigated. Methods: A retrospective medical records review was conducted to identify patients in a multicenter healthcare system who received IVIG over a 10-year period and had serum IgG measurements within two days before and two days after the date of IVIG administration. For each of the 11 adults and 7 adolescents identified, the relationship between the weight-based dose of IVIG (determined using actual body weight [BW], adjusted BW, or ideal BW [IBW]) and the resulting change in serum IgG was evaluated. Correlation coefficients and corresponding p values for the three dosing methods were calculated and compared. Results: Among adult patients, the correlation of IVIG dose and postdose change in serum IgG was strongest with dosing by IBW (correlation coefficient [ r ], 0.83 [ p < 0.05] versus r values of 0.73 and 0.70 for dosing by adjusted BW or actual BW, respectively [ p = 0.05 for both]); the corresponding r values in adolescent patients were 0.99, 0.99, and 0.95, respectively ( p < 0.005 for all). There were no statistically significant differences between the r values calculated for the three weight-based dosing methods in either adults or adolescents. Conclusion: In adult patients, the correlation between the dose of IVIG and the change in IgG level was strongest when doses were calculated using IBW; comparable degrees of correlation were observed with the three evaluated methods of weight-based dosing in the adolescent population.